The Immunomodulatory Properties of Propyl‐Propane Thiosulfonate Contribute to its Intestinal Anti‐Inflammatory Effect in Experimental Colitis. Issue 5 (9th January 2019) - Vezza, Teresa; Algieri, Francesca; Garrido‐Mesa, José; Utrilla, María Pilar; Rodríguez‐Cabezas, María Elena; Baños, Alberto; Guillamón, Enrique; García, Federico; Rodríguez‐Nogales, Alba; Gálvez, Julio
Abstract : Scope: Propyl‐propane thiosulfonate (PTSO) is a component isolated from garlic ( Allium sativum ) with antioxidant, anti‐inflammatory, immunomodulatory, and antimicrobial properties. In consequence, PTSO can be a potential candidate for the treatment of inflammatory bowel diseases. Methods and results: The anti‐inflammatory effects of PTSO are studied in two mice models of colitis: 2, 4‐dinitrobenzene sulfonic acid (DNBS) (PTSO doses: 0.01–10 mg kg –1 ) and dextran sodium sulfate (DSS) (PTSO doses: 0.01–0.1 mg kg –1 ). The immunomodulatory effects of PTSO (0.1–25 µm ) are also shown in vitro in Caco‐2 and THP‐1 cells, reducing the production of pro‐inflammatory mediators and downregulating mitogen‐activated protein kinases (MAPKs) signaling pathways. This compound displays beneficial effects in both models of mouse colitis by reducing the expression of different pro‐inflammatory mediators and improving the intestinal epithelial barrier integrity. Moreover, PTSO ameliorates the altered gut microbiota composition observed in DSS colitic mice. Conclusion: PTSO exerts intestinal anti‐inflammatory activity in experimental colitis in mice. This anti‐inflammatory activity can be associated with the immunomodulatory properties of PTSO through the regulation of the activity of cells involved in the inflammatory response. Furthermore, PTSO is able to restore the intestinal epithelial barrier function and to ameliorate the intestinal microbiota homeostasis, thus supporting its future development in human IBD. Abstract : Propyl‐propane thiosulfonate (PTSO) shows intestinal anti‐inflammatory properties in two experimental models of mouse colitis, 2, 4‐dinitrobenzene sulfonic acid and dextran sodium sulfate, which are associated with reduced expression of pro‐inflammatory mediators, improvement of intestinal epithelial barrier integrity, and amelioration of altered gut microbiota composition. In vitro assays in Caco‐2 and THP‐1 cells reveal that PTSO reduced the production of pro‐inflammatory mediators and downregulated mitogen‐activated protein kinases signaling pathways.